2006
DOI: 10.1007/s11010-006-9308-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hnRNP C1/C2 by siRNA sensitizes HeLa cells to various stresses

Abstract: The heterogeneous nuclear ribonucleoprotein C1/C2 is one of the most abundant proteins in the nucleus, and shown to have roles in cellular differentiation and proliferation through post-transcriptional regulations of certain mRNA species. We studied its role in stress response using siRNA mediated knockdown approach in HeLa cells. Upon transient transfection with plasmid encoding siRNA, the cells showed increased sensitivities to various chemical agents, namely H(2)O(2, )paraquat, camptothecin, ICRF-193 and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Down-regulation of the hnRNP C1/C2 protein amount was reported in acute promyelocytic leukaemia upon treatment with all-transretinoic acid (Harris et al 2004). Decrease in hnRNP C1/ Protein spots concordantly identified in the c-myc-downregulated as well as the control group are marked bold C2 levels itself was correlated to higher sensitivity towards chemical stress (Hossain et al 2007). HnRNP C1/C2 was proven to bind to p53 mRNA and this binding is strongly enhanced in response to cytotoxic drugs, which increase cytosolic hnRNP C1/C2 levels (Christian et al 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Down-regulation of the hnRNP C1/C2 protein amount was reported in acute promyelocytic leukaemia upon treatment with all-transretinoic acid (Harris et al 2004). Decrease in hnRNP C1/ Protein spots concordantly identified in the c-myc-downregulated as well as the control group are marked bold C2 levels itself was correlated to higher sensitivity towards chemical stress (Hossain et al 2007). HnRNP C1/C2 was proven to bind to p53 mRNA and this binding is strongly enhanced in response to cytotoxic drugs, which increase cytosolic hnRNP C1/C2 levels (Christian et al 2008).…”
Section: Discussionmentioning
confidence: 90%
“…The hnRNP C proteins, which belong to a large family of RNA motif-binding RNPs, are among the most abundant nuclear proteins involved in mRNA biogenesis, DNA repair [31,32], the cell cycle, apoptosis [33,34], and the maintenance of cellular homeostasis [35]. In normal proximal internal carotid arteries, hnRNP C proteins are expressed predominantly in the endothelium, with significantly lower expression in medial smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It is a compo- nent of the spliceosome complex (38), and a recent study using a hnRNP C knockdown approach identified BCL2L12 and PCBP4 as genes whose splicing is regulated by hnRNP C (39). Additional functions, such as regulating telomerase activity (40), XIAP translation through the IRES promoter (41), and response to hydrogen peroxide stress (42,43) have been attributed to hnRNP C. The interaction of PTEN with hnRNP C and the complex assembly may be important in regulating these known hnRNP C functions.…”
Section: Discussionmentioning
confidence: 99%